Continuous one-dimensional elastic macro-elements as a natural alternative crack detection tool to the spectral finite element method (Archives of Mechanics - Test, 2007)
In the paper the wave method of fault identification in rods, shafts and beams is proposed. This method is based on dynamical models consisting of structural macro-elements with continuously distributed inertial-visco-elastic properties, represented by individual segments of the investigated objects. The fault detection and identification reduces to simulations of diagnostic wave propagation and wave reflections in these models. These simulations are performed directly in time domain by means of analytical solutions of the partial differential equations of motion. In the computational examples, reflected waves were sought in the cracked cantilever rod and beam. These results have been compared with the analogous findings obtained by other authors, using the spectral finite element method. The natural continuous character of the applied elastic macro-elements enables us to apply a straightforward simulation of wave effects, which makes the proposed approach a promising and effective tool for fault identification in various structures and mechanical systems.